High-frame rate and high-count rate hybrid pixel detector for 4D STEM applications - Zambon, P.; Vávra, J.; Montemurro, G.; Bottinelli, S.; Dudina, A.; Schnyder, R.; Hörmann, C.; Meffert, M.; Schulze-Briese, C.; Stroppa, D.; Lehmann, N.; Piazza, L. (Frontiers in Physics, 2023)
This study presents the performance assessment of a novel hybrid pixel detector. The electron counting application-specific integrated circuit (ASIC), named KITE, was optimized for 4D STEM applications and bump-bonded to a silicon sensor that is suitable for electron energies in the range 30–200 keV. The KITE ASIC was developed for high frame rates, currently up to 120 kfps, and high count rates, owing to fast signal shaping times and instant retrigger technology, which allows operation in a unique non-paralyzable counting mode. Investigated quantities include the spectral response, the identification of optimal threshold energies, an estimation of the threshold trimming accuracy, the analysis of the single-event multiplicity distributions, the count rate capabilities, and imaging performance metrics MTF and DQE. To highlight the capabilities of the detector, the best value of 10% of linearity loss was achieved at 84 Mcts/s/pix, the best value of count rate “cutoff” at nearly 150 Mcts/s/pix, and DQE (0) between 0.75 and 0.82 up to the electron energy of 160 keV.